Searching for Basic Consumption Patterns Is the Engel Elasticity of Housing Unity? - Erling Røed Larsen (Statistics Norway, Research Department, 2002)
We estimate Engel elasticities of housing expenditures for each independent cross-section of the Consumer Expenditure Surveys in the period 1986-1998, and find that the elasticity remains close to unity for all years. Its mean over the period is 1.02. Engel and demographic effects for housing are estimated in an errors-in-variables two stage least square regression model using random samples of Norwegian households. We find that given demographic composition household demand for housing seems to increase proportionately with total consumption, in contrast to other categories such as food and transportation. The empirical regularity between housing expenditures and total consumption yields forecasting potential and may represent a basic pattern of consumption.
Keywords: D12; R21; 330; Budget share; consumption pattern; demand for housing; Engel elasticity